2018
DOI: 10.1097/prs.0000000000004167
|View full text |Cite
|
Sign up to set email alerts
|

Deferoxamine Preconditioning of Irradiated Tissue Improves Perfusion and Fat Graft Retention

Abstract: The authors' results demonstrated increased perfusion with deferoxamine treatment, which was also associated with improved fat graft volume retention. Preconditioning with deferoxamine may thus enhance fat graft outcomes for soft-tissue reconstruction following radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…Prior studies in mice have shown promise for use of DFO in the treatment of RIF 38 . Serial injections of DFO into irradiated tissue prior to fat grafting was observed to increase perfusion in the overlying skin and improve retention of fat graft volumes, thereby mitigating some of the detrimental fibrotic effects of radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies in mice have shown promise for use of DFO in the treatment of RIF 38 . Serial injections of DFO into irradiated tissue prior to fat grafting was observed to increase perfusion in the overlying skin and improve retention of fat graft volumes, thereby mitigating some of the detrimental fibrotic effects of radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were randomized into four experimental groups on the first day of patch placement: (1) IR alone (IR only, n = 8), (2) DFO treatment for two weeks after recovery from IR (DFO post-IR, n = 4), (3) DFO prophylaxis with treatment through and post-IR (DFO ppx, n = 8), or (4) no irradiation or DFO (No IR, n = 4). Mice in the DFO post-IR group were treated with DFO for two weeks, beginning after a 4-week recovery period following completion of IR, adapted from a protocol described by Flacco et al 38 . Patches were changed daily for the 14-day treatment period.…”
Section: Animals Female Adult 60-day-old Cd-1 Nude Immunocompromisedmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Inadequate tissue vascularization is the main cause of low graft survival. 6 Flacco et al 7 demonstrated that deferoxamine preconditioning improves perfusion and fat graft retention. Okyay et al 8 proved that treatment of fat grafts with the selective beta-1-blocker metoprolol resulted in a good quality graft.…”
Section: Introductionmentioning
confidence: 99%